Trial of a Peer to Peer Play-based Intervention to Improve Social Play Skills for Children with Autism Spectrum Disorder - Kent, Cally Frances (Curtin University, 2019)
This thesis evaluated a play-based peer-mediated intervention for children with Autism Spectrum Disorder (ASD) to improve their play performance using a systematic approach to intervention development and evaluation. The randomised controlled trial demonstrated a significant, moderate effect on play performance for children with ASD and their typically developing peers. Intervention effects were maintained for three-months and generalised to the home environment. Introducing a third peer produced mixed results and provides direction for future research.